INFLUENCE OF BIOFERTILIZERS ON RATE OF DECOMPOSITION AND NUTRIENT RELEASE FROM LITTER OF CRACK WILLOW (SALIX FRAGILIS) UNDER TEMPERATE HIMALAYAN CONDITIONS - MALIK ASIF; M.Y.ZARGAR (International Journal of Pharma and Bio Sciences, 2013)
This study was carried out at the forest nursery of Department of Forestry, Faculty of Agriculture and Regional Research Station, Wadura SKUAST-K, Sopore, Kashmir during 2006 and 2007 to examine the role of live biofertilizers in litter decomposition and nutrient release in Salix fragilis under natural Salix stands. The experiment was laid in completely randomised design with three replications which comprised five treatment combinations of 5 inoculants (no-inoculant; Azotobacter, Chroococcum, Pseudomonas fluorescens, effective microorganisms and combinations of Azotobacter chroococcum + Pseudomonas fluorescens + effective microorganisms). Higher rate of decomposition of Salix fragilis litter was recorded in June (89.29%). Lower rate of decomposition of the species was recorded in January (39.07%). Plant N, P, K, Ca, and Mg release showed an increasing trend from July onwards upto November and immobilization of above nutrients was observed in December and January. However, in the succeeding months an increasing trend in the nutrient release was observed. Highest nutrient release was recorded under combined inoculation of Azotobacter chrococcum + Psedomonas fluorescens + effective microorganisms followed by effective microorganims as compared to other treatments and control. Combined biofertilizer inoculation resulted in a significant increase in total viable bacteria, fungi and actinomycetes followed by effective microorganisms, Pseudomonas fluorescens, Azotobacter chroococcum and control respectively. Thus the treatment combination of Azotobacter choococcum + Pseudomonas fluerescens + effective microorganisms proved to be the best for decomposition of Salix fragilis litter and nutrient release.